Paroan Hasil Pertanian Perspektif Akad Muzara’ah - Siti Masriyah; Lifia; Ahmad Djalaluddin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this study was to ascertain the agricultural product sharing system from the standpoint of a muzara'ah contract. In order to examine the empirical reality behind reality and facts in depth and in more detail, this research employs a descriptive qualitative approach. This type of research uses research methods that concentrate on actual problems as they existed at the time of the research and was thought to be particularly appropriate for the topic of the title. Qualitative research is research with data that does not use numbers but is descriptive. This study focuses on the role that muzara'ah contracts have in the agricultural product sharing system. The findings of this study suggest that the majority of people who utilize the paraon method in their contracts make them verbally without any written proof and simply rely on trust between the parties. East Dempo Village has two different models for the allocation of crops. Sacks are used as the primary distribution method in the first model. The simulation when the two divisors are allocated as cash.